Faktor Penyebab Terjadinya Duplikasi Nomor Rekam Medis Pasien - Riska Rosita; Rini Apriyani (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2023)
The medical record numbering system is a procedure for writing the number given to patients when they come for treatment at a health service. Based on observations at the Toboali Health Center, there were 13 patients who had more than one medical record number, there were also 14 cases where one medical record number was used for more than one patient. The purpose of this study was to determine the factors that cause duplication of patient medical record numbers. The research method is descriptive using a cross sectional survey design approach. The results showed that the causes of duplication of patient medical record numbers consisted of regulations/policies, facilities and infrastructure, human resources, patient compliance with MNH and changes in patient data that were not confirmed. The conclusion of this study is that all of these causal factors must be suppressed so that the history of patient data becomes continuous and prevents the risk of medical errors or malpractice.